Empirical Review Causes Of Hit And Run That Lead To The Victims Death - Devina Sesilia Ginoga (Universitas Negeri Gorontalo, 2021)
This study aims to determine the cause of the hit and run resulting in the victim's death. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling. The results of this study indicate that the causes of hit-and-run resulting in the victim's death are basically caused by several things, including First, the lack of legal awareness of the perpetrators, this is certainly influenced if they do not have formal education. The two perpetrators were afraid when they experienced a collision, so according to him, to avoid the legal process and public outcry, the solution was to run away from responsibility for their actions. Third, the streets are quiet so that when you are driving a motorbike it exceeds the average speed. Handling traffic by creating accident-prone service posts in accident-prone areas, and deploying traffic accident service centers to make it easier for the public to report traffic accidents, especially hit-and-run.